IMPLEMENTASI PERATURAN BUPATI NOMOR 81 TAHUN 2021 OLEH DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DALAM PERBAIKAN JALAN DI KABUPATEN KAMPAR TAHUN 2024 (STUDI DI KECAMATAN BANGKINANG KOTA) - Kurniawan, Rudy; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research aims to analyze the implementation of Regent Regulation Number 81 of 2021 by the Kampar Regency Public Works and Spatial Planning (PUPR) Department in road repairs in Bangkinang Kota District. Repair and maintenance of road infrastructure has an important role in supporting community mobility and regional economic growth. This research uses George C Edward III's theory, divided into 4, namely communication, resources, disposition and bureaucratic structure. This research uses a qualitative method with a descriptive approach. The types of data are primary data and secondary data, primary data is obtained directly from informants. Meanwhile, secondary data is data that supports or strengthens primary data. Data collection techniques were carried out using interviews and documentation. There are 4 stages of data analysis techniques used, namely data collection, data reduction, data presentation and drawing conclusions. The results of this research show that the implementation of Kampar Regent Regulation Number 81 of 2021 has been carried out through several stages, including identifying damaged road sections, preparing repair plans, and implementing road rehabilitation projects. Factors that support the successful implementation of this policy include the existence of clear regulations, human resource support, and supervision carried out by the relevant agencies. However, there are obstacles such as budget limitations, lack of communication and coordination between agencies, and low community participation in monitoring infrastructure projects. Keywords: Implementation, Policy, Road Infrastructure.